2019
DOI: 10.1186/s13048-019-0574-5
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 promotes expression of the ST6Gal-I glycosyltransferase in ovarian cancer cells

Abstract: Background: The ST6Gal-I glycosyltransferase, which adds α2-6-linked sialic acids to N-glycosylated proteins is upregulated in a wide range of malignancies including ovarian cancer. Prior studies have shown that ST6Gal-Imediated sialylation of select surface receptors remodels intracellular signaling to impart cancer stem cell (CSC) characteristics. However, the mechanisms that contribute to ST6Gal-I expression in stem-like cancer cells are poorly understood. Results: Herein, we identify the master stem cell t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 92 publications
3
24
0
Order By: Relevance
“…SOX2 has been involved in numerous cancers, such as prostate cancer, ovarian cancer, and breast cancer. 25 , 26 , 27 Concurred with our results, a prior study indicated SOX2 upregulation in EC samples and that SOX2 overexpression enhanced EC cell proliferation and invasion. 28 Meanwhile, a study by Ishida et al.…”
Section: Discussionsupporting
confidence: 88%
“…SOX2 has been involved in numerous cancers, such as prostate cancer, ovarian cancer, and breast cancer. 25 , 26 , 27 Concurred with our results, a prior study indicated SOX2 upregulation in EC samples and that SOX2 overexpression enhanced EC cell proliferation and invasion. 28 Meanwhile, a study by Ishida et al.…”
Section: Discussionsupporting
confidence: 88%
“… 22 Hypersialylation is associated with, and suggested to be causal to, increased aggressiveness, stemness, resistance to chemotherapeutic agents, ability to survive in stressful conditions like hypoxia, and impaired nutrient supply. 24 , 25 , 27 , 41 However, when we performed flow cytometry to isolate the two subpopulations showing distinct α2,6-sialic acid levels, the one showing lower levels (which we denoted as medium 2,6-Sial cells) showed greater invasion than high 2,6-Sial cells both in the transwell assay and in 3D cultures. Medium 2,6-Sial cells were also observed to adhere better to both laminin-rich and collagenous ECM, as well as migrate through the latter with higher velocity compared to high 2,6-Sial cells.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of SOC is a complex process that is driven by specific genetic and epigenetic alterations. For example, elevated ST6GAL1 expression and hypermethylation of RASSF1A have been demonstrated to play critical roles in ovarian cancer (20,21). The present study aimed to identify the core genes and significant gene sets for SOC to improve the understanding of the potential molecular mechanisms, which may help develop novel biomarkers or therapeutic targets for this disease.…”
Section: Discussionmentioning
confidence: 99%